PERSEPSI DAN PERILAKU KONSUMSI OBAT HERBAL PENDERITA DIABETES MELLITUS TIPE 2 DI DESA PESISIR KECAMATAN GENDING KABUPATEN PROBOLINGGO - Rahmat, Nafolion Nur; Hartono, Dodik; Laili, Nurul (STIKes Maharani Malang, 2020)
ABSTRACT Introduction: Diabetes mellitus has complicated health problems with various causes and various treatments that must be performed. Various myths can affect treatment and may use traditional medicines, such as the consumption of herbal medicines for health care. The aim of the investigation was to explore the perception and consumption of herbal drugs in diabetic patients living in the community in Pesisir Village Gending Probolinggo City. Metho: The study was conducted in the Coastal Village of Gending Subdistrict, Probolinggo Regency in January 2020. The type of research used in this study was a correlational analytic study with a cross sectional approach. The data collection process uses open questions about consumption of herbal medicines and their perception of herbal medicines for DM. The data collection method uses a questionnaire sheet that was distributed to 28 respondents with DM with different characteristics. The selection of respondents is done by the total sampling method. The questionnaire is filled in somewhere and done simultaneously by inviting respondents. Results and Analysis: The 28 respondents who answered the questionnaire, 100% reported having used herbal medicine to manage their diabetes, and 78.6% reported using conventional medicine and traditional medicine in combination. Some respondents believe that combining traditional and traditional medicines increases the effectiveness of treatment. Reasons given for using traditional medicines include the high cost of traditional treatments and the availability and accessibility of traditional medicines. The most commonly used herbal medicines are Moringa oleifera leaves, Soursop (Annona muricata), Pare (Momordica Charantia), Chinese Pumpkin (Lagenaria siceraria), Mangosteen (Garcinia mangostana), Cinnamon (Cinnamomum Verum), and Cumin black (Nigella sativa). Discussion: Further research on herbal medicines is needed to identify the bioactive compounds and metabolites present in the most commonly consumed herbal drugs and their benefits